Additions to the knowledge of Taeniogonalos Schulz, 1906 (Hymenoptera: Trigonalyidae) from India with the description of a new species from Western Ghats - Kumar, P. Girish; Hegde, V.d. (Zootaxa, 2023)
A new species of Taeniogonalos Schulz, namely, Taeniogonalos dhritiae Girish Kumar & Hegde sp. nov., is described from the Western Ghats, India. A revised key to Indian species is provided.